2018
DOI: 10.1080/2162402x.2018.1494108
|View full text |Cite
|
Sign up to set email alerts
|

Bovine herpesvirus 4-based vector delivering the full length xCT DNA efficiently protects mice from mammary cancer metastases by targeting cancer stem cells

Abstract: Despite marked advancements in its treatment, breast cancer is still the second leading cause of cancer death in women, due to relapses and distal metastases. Breast cancer stem cells (CSCs), are a cellular reservoir for recurrence, metastatic evolution and disease progression, making the development of novel therapeutics that target CSCs, and thereby inhibit metastases, an urgent need. We have previously demonstrated that the cystine-glutamate antiporter xCT (SLC7A11), a protein that was shown to be overexpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 62 publications
1
43
0
Order By: Relevance
“…In a similar way, a newer VLP vaccine that displays the third extracellular domain of xCT (ECD3), whose sequence is longer than that of ECD6, resulting in a major oligoclonal antibody response, can neutralize xCT function and impair breast cancer cell proliferation and metastasization [ 61 ]. Finally, the bovine herpesvirus 4 (BoHV-4)-based anti-xCT vaccine, which exploits a safe viral vector that confers immunogenicity to tumor antigens, has proven to be effective in impairing lung metastasis and inducing T lymphocyte activation, anti-xCT antibody production and ADCC in mouse mammary cancer models [ 53 ]. It is worth noting that anti-xCT vaccination impairs metastasis formation in a spontaneous mouse model of HER2 + mammary cancer, and synergizes with HER2-targeted therapies [ 56 ].…”
Section: The Cystine/glutamate Antiporter Xctmentioning
confidence: 99%
“…In a similar way, a newer VLP vaccine that displays the third extracellular domain of xCT (ECD3), whose sequence is longer than that of ECD6, resulting in a major oligoclonal antibody response, can neutralize xCT function and impair breast cancer cell proliferation and metastasization [ 61 ]. Finally, the bovine herpesvirus 4 (BoHV-4)-based anti-xCT vaccine, which exploits a safe viral vector that confers immunogenicity to tumor antigens, has proven to be effective in impairing lung metastasis and inducing T lymphocyte activation, anti-xCT antibody production and ADCC in mouse mammary cancer models [ 53 ]. It is worth noting that anti-xCT vaccination impairs metastasis formation in a spontaneous mouse model of HER2 + mammary cancer, and synergizes with HER2-targeted therapies [ 56 ].…”
Section: The Cystine/glutamate Antiporter Xctmentioning
confidence: 99%
“…In 2018, Bolli et al showed that inhibition of xCT by virus-like-particle immunotherapy could reduce the metastatic potential of breast cancer stem cells [316]. Vaccines targeting SLC7A11 have been developed and demonstrated to protect mice from mammary cancer metastases [317,318].…”
Section: Slc7a11 In Breast Cancermentioning
confidence: 99%
“…The BoHV-4 TK genomic region is strongly conserved among BoHV-4 isolates [15], therefore ensuring the stability of the genomic locus from potential recombination when foreign DNA sequences are inserted. Previous studies have shown that interrupting the TK locus by the insertion of foreign DNA sequences [53] of different sizes does not interfere with viral replication in vitro and heterologous protein expression is maintained [36,37,39,[41][42][43][44]54,55]. However, the inactivation of herpesvirus TK gene results in severe attenuation in vivo [54,56,57]; reducing the risks associated to the use of herpesviral vectors [58,59].…”
Section: Generation Of Recombinant Bohv-4 Vectors Delivering Niv F Anmentioning
confidence: 99%
“…Lastly, BoHV-4 can be manipulated using infectious BoHV-4-derived bacterial artificial chromosome (BAC) genomes cloned in Escherichia coli as a tool to readily modify the viral genome [36]. Recombinant BoHV-4 vectors expressing heterologous antigens have been shown to be immunogenic and efficacious in mice [37][38][39][40][41], sheep [42], rabbits [43], goats [44], and pigs [45].…”
Section: Introductionmentioning
confidence: 99%